2017
DOI: 10.1186/s12932-017-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between magnetite and humic substances: redox reactions and dissolution processes

Abstract: Humic substances (HS) are redox-active compounds that are ubiquitous in the environment and can serve as electron shuttles during microbial Fe(III) reduction thus reducing a variety of Fe(III) minerals. However, not much is known about redox reactions between HS and the mixed-valent mineral magnetite (Fe3O4) that can potentially lead to changes in Fe(II)/Fe(III) stoichiometry and even dissolve the magnetite. To address this knowledge gap, we incubated non-reduced (native) and reduced HS with four types of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
(69 reference statements)
0
22
0
Order By: Relevance
“…Dissolution of the solid phase and an increase in dissolved Fe 2+ and/or Fe 3+ as a result of incubation of MNPs with humic substances was demonstrated by Sundman et al in [71]. Authors revealed that the magnetite incubated with native humic substances becomes more oxidized as compared with a control magnetite [71].…”
Section: The Relative Bioluminescence Intensity I Relmentioning
confidence: 95%
See 2 more Smart Citations
“…Dissolution of the solid phase and an increase in dissolved Fe 2+ and/or Fe 3+ as a result of incubation of MNPs with humic substances was demonstrated by Sundman et al in [71]. Authors revealed that the magnetite incubated with native humic substances becomes more oxidized as compared with a control magnetite [71].…”
Section: The Relative Bioluminescence Intensity I Relmentioning
confidence: 95%
“…However, remarkable variations in zeta potential are not observed likely due to the lower sensitivity of the electrophoretic light scattering method in comparison with the cellular sensitivity. Sensitive Mossbauer spectroscopy showed minor changes in composition of solid Fe 3 O 4 -HA due to iron ions release [71,72].…”
Section: Effects Of Mnps On Bacterial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such humic substances have been shown to be able to shuttle electrons to and from both biogenic and chemically synthesized magnetites. 236 Furthermore, the identity of the mineral phases produced by the Fe(III)-reducing strain Shewanella oneidensis MR-1 has been shown to be dependent upon other physico-geochemical factors including geometric orientation of the bottles that the bacteria and minerals are incubated in, with magnetite formation favoured when the ferrihydrite pellet was most dense. 235 In the environment, microbial magnetite has been shown to form at hydrocarboncontaminated field sites and was even used by its magnetic signal to locate the hotspot of microbial activity.…”
Section: Synthesis By Bacterial Fe(iii) Reductionmentioning
confidence: 99%
“…By experimental analysis and density functional theory (DFT) calculations, Kubicki et al simulate interactions between chromate and a ferrihydrate nanoparticle [4]. Then, several articles by Sowers et al [5], Stuckey et al [6], Sundman et al [7], and Zhu et al [8] discuss how iron and manganese (hydr)oxides interact with organic compounds undergoing redox reactions and dissolution. In addition, Cade-Menun et al [9] and Hamilton et al [10] investigate the fate and transport of phosphate as a nutrient in soil systems by using inductively coupled plasma spectroscopy, P-nuclear magnetic resonance, and X-ray absorption spectroscopy.…”
mentioning
confidence: 99%